Про виховання мовної свідомості - Селігей, П.О. (Мовознавство, 2010)
Стаття порушує проблеми мовного виховання громадян України. Розглянуто його засади, методи, канали й основний зміст. Наголошено, що піднесення мовної свідомості стає нині конче важливим з огляду на перспективи мовного майбутнього людства. The article deals with problems of linguistic upbringing of Ukrainians. Its principles, methods, channels, and main content are analyzed. It is accentuated, that the growth of linguistic consciousness becomes very important nowadays in connection with perspectives of linguistic future of humankind.